The Treuhandanstalt in interregional competition - FRIEDRICH, Peter; LJNDEMANN, Steffen (European Spatial Research and Policy, 1999)
In Germany business promotion is pursued within vertical and horizontal nets of regional competition. The main competitors are business promotion agencies and business promotion offices, including Treuhand (Treuhandanstalt) or BvS. In eastern Germany oligopolistic market forms of horizontal regional competition in business promotion prevail. A model of vertical competition between the Treuhand, a town, and a private firm has been constructed to explain real estate price formation. In a two region model of fiscal regional competition in a federation, the regions apply different fiscal policies in order to maximise regional income. Fiscal policy of the federal government does influence the income positions of the regions. The Treuhandanstalt can be interpreted as a federal business promotion measure of deficit spending.